Korotko’s phenomenological myth of Odesa in Bera and Cucumber: otherness, melancholy and anthropocene - Drozdovskyi, Dmytro; Naumenko, Nataliia (My University, 2024)
In the research, with the help of the method of mytho-criticism and archetypal analysis (Carl Gustav Jung), the author has analyzed and outlined the chronotope represented in the stories in Bera and Cucumber by Aleksandr Korotko. This book, translated into English by M. Pursglove, was published in London in 2023. With the help of archetypal analysis, the Odesa text was characterized as a mythological one. It has been investigated that the Odesa narrative represents a special worldview of the heroes, who are characterized by a combination of kabbalistic worldview, Christian humanism, Turkish melancholy, contemplativeness that results from the unity of the heroes of the Odesa space with eternal nature elements

У дослідженні за допомогою методу міфокритики та архетипного аналізу (Карл Густав Юнг) автор проаналізував та окреслив хронотоп, представлений в оповіданнях «Бера та Огірок» Олександра Коротка. Ця книга, перекладена англійською мовою М. Персглоув, була видана в Лондоні в 2023 році. За допомогою архетипного аналізу одеський текст було охарактеризовано як міфологічний. Досліджено, що одеський наратив репрезентує особливе світовідчуття героїв, для яких характерне поєднання каббалістичного світогляду, християнського гуманізму, турецької меланхолії, споглядальності, що є результатом єдності героїв одеського простору з елементами вічної природи
Keywords: Odesa text; Odesa myth; mythocriticism; archetype; melancholy; одеський текст; одеський міф; міфокритика; архетип; меланхолія; кафедра гуманітарних дисциплін